Model Rancangan Bimbingan Kelompok dengan Metode Sosiodrama dalam Membantu Pencapaian Tugas Perkembangan Peserta Didik - Chairunnisa Rahma; Fitria Kasih; Rici Kardo (Universitas PGRI SUMATERA BARAT, 2022)
This research is motivated by the developmental tasks of students that have not been achieved. The aims of this research are to describe: 1) Profile of the achievement of students' developmental tasks in group guidance using the sociodrama method; 2) the design model of group guidance services in helping the achievement of the developmental tasks of students by using the theoretically acceptable sociodrama method. The research method used is research and development. The research population was 34 students, the research instrument used was the Inventori Tugas Perkembangan (ITP) and the data dialysis technique used the Aplikasi Tugas Perkembangan (ATP). Furthermore, the supervising lecturer as a content validator of the group guidance design model in helping the achievement of students' developmental tasks using the sociodrama method.The results of the study revealed that: 1) The achievement of students' developmental tasks on average was at the level of self-awareness development, namely 4.48; 2). The design model for group guidance services in helping students achieve the developmental tasks of using the Sociodrama method is theoretically acceptable. Keywords: Group guidance, sociodrama, developmental.